Heat Shock Proteins as Key Triggers to Form Cryopreserved Progenitors-Derived Tolerogenic Dendritic Cells - Kisielova, Hanna; Dubrava, Tetiana; Goltsev , Anatoliy (Problems of Cryobiology and Cryomedicine, 2023)
Probl Cryobiol Cryomed 2023; 33(2):144-149